Impact of urban development and land use changes on the climate of the city of Shiraz and Fasa - Ahmad Mazidi; Mahdi Narangifard (تحقیقات کاربردی علوم جغرافیایی)
Expansion of urban areas has impacted on climate in local and global scale. As a result, residents’ life would be influenced accordingly. In this study, the effects of changes in land cover and land use change on climate of Shiraz and Fasa were studied in a long-term period. To ensure the normal data, Kolmogrov-Smirnoff test was employed. The minimum and maximum temperature parameters and relative humidity were evaluated using non-parametric Mann-Kendall and regression method in a 45-year period (1966-2010). The results showed a decreasing trend for the minimum temperature and humidity for Fasa and minimum and maximum relative humidity for Shiraz whereas other quantities showed an increasing trend. The study examined the effects of land use changes and land cover types in the 23-year period (1987-2010) using images of LANDSAT satellite of TM sensor on temperature pattern in two cities. During these 23 years, a reduction of 113 square kilometers for barren land of Shiraz and 5/7 square kilometers for barren land of Fasa and extending 110 kilometers residential users and 3/5 square kilometers in Shiraz and Fasa were reported.